Arabic Traces in the Hebrew Writing of Arab Authors in Israel - Shakkour, Aadel (Cambridge Scholars Publisher, 2021)
This book provides pioneering research on the Hebrew writings of Arab authors in Israel. It shows how authors in their Hebrew writings try to give their characters an authentic air and to create an atmosphere of authentic culture, and highlights archaic Hebrew syntactic structures that are similar to their Arabic counterparts in order to transmit Arab cultural elements. Language, after all, also serves to mediate between cultures, in addition to its function as a means of medium of communication.The text shows how Arab writers, through their translations point, to Arab culture as a possible mo.